DIGITAL PLATFORMS AS MEANS OF POLITICAL PROPAGANDA: THE CASE OF THE PROTEST AGAINST DICTATORSHIP FAKE FACEBOOK PAGE - Petrović, Dalibor (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
Growing distrust in the mainstream media has led to rising importance of cyberspace in creation of the public sphere. This is especially visible in networked autocracies, regimes that have established firm control over mainstream media, but who have also developed effective strategies and techniques to fight against political opponents on digital platforms. In the networked autocracies one can observe a development of specific type of political propaganda that can be characterized as computational propaganda. This type of propaganda is created with the help of digital platforms, political bots and the Internet of Things. The basic role of computational propaganda is not based on delivering of a positive image of the one in whose name it is being implemented, but pollution and polarization of public spaces of the Internet, with the goal to discourage as many people as possible from online political activism. Serbia is one of the countries with a highly developed computational propaganda, whether we are talking about the number of people who perform this type of propaganda in the name of the ruling majority, or we are talking about the scope of their actions. One of examples of their internet operations was launching a fake Facebook page of the Protest against the dictatorship, with the aim of confusing supporters of this protest. Our empirical study has shown that cyber troupes of the ruling majority, known as bots, have been very successful in conducting their online campaign which contributed to the end of one of the greatest anti-government protests in the post-Milosevic era.